2019
DOI: 10.1186/s41182-019-0147-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of quinolone resistance genes among extended-spectrum β-lactamase (ESBL)-producing Escherichia coli strains isolated from urinary tract infections

Abstract: Background As an opportunistic pathogen, Escherichia coli ( E. coli ) is widely recognized as the main cause of nosocomial infections as well as some disorders especially those associated with urinary tract infections (UTIs). This study, therefore, sets out to determine the extent of antibiotic resistance to quinolones and to measure the frequency of qnr genes (A, B, and S) within extended-spectrum beta-lactamase (ESB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
26
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
8
26
5
Order By: Relevance
“…Probably, communication between pathogenic and commensal bacteria and indirect exposure of commensal ora to antibiotics caused high AMR in the community. As reported by the European Antimicrobial Resistance Surveillance Network (EARS-Net), MDR among infectious E. coli isolates ranged from approximately 1% in 2002 to 4.8% in 2016 and 10.1% in 2018 [37]; however, in our study, MDR was found to be 36%, which is disconcerting. The carriage of commensal AMR, MDR and ESBL-producing isolates in healthy children under three years of age mostly re ects exposure to contamination in the family environment, water, and food rather than increased direct exposure to antimicrobial drugs [38].…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Probably, communication between pathogenic and commensal bacteria and indirect exposure of commensal ora to antibiotics caused high AMR in the community. As reported by the European Antimicrobial Resistance Surveillance Network (EARS-Net), MDR among infectious E. coli isolates ranged from approximately 1% in 2002 to 4.8% in 2016 and 10.1% in 2018 [37]; however, in our study, MDR was found to be 36%, which is disconcerting. The carriage of commensal AMR, MDR and ESBL-producing isolates in healthy children under three years of age mostly re ects exposure to contamination in the family environment, water, and food rather than increased direct exposure to antimicrobial drugs [38].…”
Section: Discussioncontrasting
confidence: 65%
“…According to a report by Castanheira et al the rates of CR in pathogenic Enterobacteriaceae increased from 0.6% in 1997-2000 to 2.9% in 2013-2016. In our study, the rate of CR in commensal E. coli strains was 1.6%; however, we do not have the exact rate of CR in pathogenic Enterobacteriacea [37].…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations